THE INFLUENCE OF SELF EFFICACY ON STUDENT LEARNING MOTIVATION IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN YOGYAKARTA CITY PUBLIC JUNIOR HIGH SCHOOLS - Isnaini, Rista; Shelly Andari (Edu Learning : Journal of Education and Learning, 2024)
This study is to determine the effect and how much effective contribution of self-efficacy on learning motivation in students at junior high schools in Yogyakarta City. The data obtained in this study through the results of a questionnaire questionnaire using a Likert scale. The subjects in this study totaled 347 students. This type of research is quantitative. Hypothesis testing using simple regression analysis on the SPSS 23 program with a significant level of p = 0.05. The results of this study indicate that (1) students' self-efficacy in public junior high schools in Yogyakarta City is in the moderate category. (2) student learning motivation in public junior high schools in Yogyakarta City is in the moderate category. (3) there is a positive and significant effect of Self efficacy on student learning motivation in schools at the State Junior High School level in Yogyakarta City, Self efficacy provides an effective contribution to student learning motivation in schools at the State Junior High School level in Yogyakarta City by 10%. The existence of Self efficacy in students can foster high motivation to achieve goals. Keywords: Self efficacy, student learning motivation, learner management.